The effect of calling on job autonomy: the moderating role of obsessive passion - Gülbahar, Yasemin; Özkan, Osman Seray (Serbian Journal of Management, 2025)
Even though research on calling in the organizational environment is the most experienced and recently remarkable issue, our information about its results is still limited due to its intense emotional nature. In particular, there is a need for studies in the context of the relationship between job autonomy in the organizational environment. To analyze the relationships and organizational consequences of the two concepts, we established a structural model which studies the effects of calling on job autonomy through obsessive passion. In order to measure the effects of concepts in different cultures, the sample of the research was selected from hotel managers in the tourism sector in Nevşehir, Turkiye. According to the data obtained from the analyzes based on 314 participants (senior managers) from the sample group consisting of 35 hotels and apart hotels, the effect of living a calling on job autonomy was significant and obsessive passion had a moderating role in the relationship between living a calling and job autonomy. Important data on the results of calling have been reached. The results support the literature. As it has been shown in previous studies, the calling is closely related to a perception of competence and when the perception of job autonomy is strong, the feeling of calling increases, which is also supported by this study. And it has been shown that the strength of this relationship is increased by obsessive passion.